Determination of efficacy of the cellular cardiomyoplasty, using navigation system NOGA XP - S. І. Estrin; T. V. Kravchenko; A. R. Pechenenko (Клінічна хірургія)
Objective. Improvement of the treatment results in patients with refractory angina, complicated by the heart insufficiency, using new methods of correction of the heart pumping function elaborated.